Effects of concomitant use of hydrogen water and photobiomodulation on Parkinson disease: A pilot study. Issue 4 (29th January 2021) - Hong, Chien-Tai; Hu, Chaur-Jong; Lin, Hung-Yu; Wu, Dean
Abstract: Background: Parkinson disease (PD), the second most common neurodegenerative disease, has no cure or applicable disease-modifying approach, only symptomatic therapy. Oxidative stress and mitochondrial dysfunction play key roles in PD pathophysiology. Animal studies have demonstrated that photobiomodulation (PBM) may enhance mitochondrial function and boost adenosine triphosphate production, thus alleviating PD symptoms; however, this process can cause increased reactive oxygen species (ROS) production. Molecular hydrogen (H2 ) is a potent and possibly therapeutic antioxidant that can mitigate the effect of ROS. PBM targeting the brainstem may facilitate neuronal activity, and the concomitant H2 may clear additional ROS produced by PBM. Therefore, this study aimed to determine the safety and effectiveness of PBM + H2 in patients with PD. Methods: We included 18 patients with PD (age 30–80 years) who were at Hoehn and Yahr stages II-III. All the participants received daily PBM + H2 therapy for 2 weeks. The adverse event and the Unified Parkinson Disease Rating Scale (UPDRS) scores were recorded. Results: We noted that the UPDRS scores began significantly decreasing from the first week, and this improvement persisted until the end of therapy. Moreover, no adverse event was recorded. After 1 week of therapy cessation, UPDRS scores slightly increased but the improvement remained significant compared with the baseline. Conclusion: This novel, proof-of-concept study demonstrated that PBM+H2 therapy is safe and reduces disease severity. A larger-scaled clinical trial is warranted to completely investigate the effects of PBM + H2 therapy on PD. Abstract : Supplemental Digital Content is available in the text